Turbulent structure of the impact of a ground vortex flow - Vieira, Diana Filipa da Conceição (2015)
Submitted by Joana Lopes Dias (jdias@ubi.pt) on 2015-06-29T16:55:49Z No. of bitstreams: 1 Dissertação de Mestrado - Diana Vieira.pdf: 11406220 bytes, checksum: 02226a69d8a7badd5b9cdca6445dab06 (MD5)